1983
DOI: 10.1073/pnas.80.14.4384
|View full text |Cite
|
Sign up to set email alerts
|

Early epochal maps of two different cell adhesion molecules.

Abstract: N-CAM, the neural cell-adhesion molecule, has previously been found to be expressed during several epochs of development and function, first as an early marker in embryo-genesis, later during organogenesis, and finally in adult life. L-CAM, the liver cell-adhesion molecule, has now been localized in embryonic and adult tissues of the chicken by fluorescent antibody techniques. In the early embryonic epoch, L-CAM and N-CAM appeared in epiblastic and hypoblastic tissues. L-CAM was distributed thereafter across a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
122
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(126 citation statements)
references
References 18 publications
4
122
0
Order By: Relevance
“…Loss of the differentiation characteristics of epithelial cells and acquisition of a more mesenchymal-like phenotype is associated with carcinoma progression (Thiery, 2002). In general, certain phenotypic alterations precipitate this transition; they include activation of several receptor tyrosine kinases, loss of E-cadherin expression, and relocalization of b-catenin (Edelman et al, 1983;Frixen et al, 1991;Miller and McClay, 1997;Morali et al, 2000;Ciruna and Rossant, 2001). Interestingly, Lamorte et al (2002) have recently demonstrated that CRKII performs a critical role in promoting an epithelial-mesenchymallike transition in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of the differentiation characteristics of epithelial cells and acquisition of a more mesenchymal-like phenotype is associated with carcinoma progression (Thiery, 2002). In general, certain phenotypic alterations precipitate this transition; they include activation of several receptor tyrosine kinases, loss of E-cadherin expression, and relocalization of b-catenin (Edelman et al, 1983;Frixen et al, 1991;Miller and McClay, 1997;Morali et al, 2000;Ciruna and Rossant, 2001). Interestingly, Lamorte et al (2002) have recently demonstrated that CRKII performs a critical role in promoting an epithelial-mesenchymallike transition in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, motile cells such as fibroblasts express N-cadherin (14) and a switch from E-cadherin to N-cadherin occurs during gastrulation when epiblast cells ingress through the primitive streak to form the mesoderm (22,23). In addition, N-cadherin has been shown to correlate with a motile, fibroblastic phenotype in squamous cell carcinomas of the head and neck (11) and in melanomas (24).…”
Section: Discussionmentioning
confidence: 99%
“…The two primary CAMs are dynamically expressed in definite sequences during development (9,11) and both appear at least transiently on derivatives of all three germ layers (12). At sites of embryonic induction there are two modes of CAM expression at the cell surface: in migrating mesenchyme, N-CAM first diminishes at the cell surface and then reappears, whereas in epithelia, both N-CAM and L-CAM appear together and one or the other subsequently disappears.…”
mentioning
confidence: 99%
“…These include two primary CAMs, the neural cell adhesion molecule N-CAM (3,4) and the liver cell adhesion molecule L-CAM (5,6), which are found very early in development, and one secondary CAM, the neuron-glia adhesion molecule, Ng-CAM, which appears on postmitotic neurons (7,8). Studies of these cell surface glycoproteins have suggested that there may be few primary CAMs (9) and that regulation of the expression of these molecules and of additional secondary CAMs may be pivotal processes in morphogenesis and histogenesis (10).…”
mentioning
confidence: 99%